Alternative products to control Hemileia vastatrix (Berkeley & Broome) and Cercospora coffeicola (Berkeley & Cooke) in organic coffee - Androcioli, Humberto Godoy; Menezes Jr., Ayres de Oliveira; Hoshino, Adriano Thibes; Androcioli, Leonardo Godoy (Coffee Science - ISSN 1984-3909, 2012)
The study was conducted in a municipality in the northern region of Parana State in the coffee cultivar IAC Icatu precoce3282 with eight years of age, grown in the spacing of 2.0 m x 0.8 m. The aim was to evaluate the influence of alternative products onCercospora leaf spot and coffee rust for use in a cultivated plantation in an organic production system. The design used was arandomized block with seven treatments, four replications and plots of 30 plants. The treatments were: negative control, chemicalcontrol (thiamethoxan cyproconazol), neem oil, silicate clay; Syrup lush; Biofertilizer EM-5 and propolis extract in the first year andpropolis extract in the second year, Kaolin/kaolin+nim in the first year and Kaolin+nim in the second year. Evaluations of Cercosporacoffeicola and Hemileia vastatrix were conducted in the period of December 2007 and June/2008 Dec/2008 to May/2009. Results inboth periods demonstrated that the chemical control and the alternative products kept the area under the incidence progression curveof C. coffeicola and H. vastatrix lower than in coffee without control of disease. All treatments were superior to control production inthe second harvest in 2009. The Control of diseases with alternative products presented much higher costs than chemical control,mainly due to the need for more manpower, indicating the need for compensation in the final product price by consumers to maintainthe organic agriculture business system competitive.